Development of vegetarian preparations based on legumes for the pre-school public (Research, Society and Development, 2021)
The present study aims to develop vegetarian preparations for preschoolers and characterize them in terms of nutritional composition and cost. A search, selection and test of 23 vegetarian preparations was carried out, with standardization of technical preparation sheets, calculation of the nutritional value and cost of the portion. Food composition tables and food guides were used. The portions of the vegetarian preparations were compared among themselves as to their nutritional composition, and with the preparations of animal origin, offered at a Child Education Center, as well as the reference values ​​of the National School Feeding Program. Of the 23 preparations developed, nine were based on chickpeas; eight of beans, peas and lentils and six of soy and textured soy protein. White bean meatballs, bean burger, soy meatballs, mini meatballs and textured soy protein stroganoff, stood out in terms of nutritional composition, with cost ranging from R$ 0.18 to R$ 0.64. The vegetarian preparations developed contributed satisfactorily to the recommendations of the National School Feeding Program and presented, for the most part, a composition superior to the evaluated animal dishes. Thus, it is possible to infer that legume-based preparations are suitable to be part of the school menu.